Autologous platelet-rich plasma action on skin autografts in horses - Pedroso,Ana Carolina Barros da Rosa (2021)
ABSTRACT: This study evaluated the action of autologous platelet-rich plasma (PRP) on cutaneous wounds, containing skin autografts, in the gluteal region of horses. Seven healthy horses were used. Two 6 x 6cm cutaneous wounds were produced on each side of the gluteal region. Eight days after wound induction, grafts were performed with skin fragments harvested from the neck, as well as the application of PRP, prepared by double-centrifugation protocol. Wounds with autografts on the left side received PRP (group T), and those with autografts on the right side did not receive treatment (group C). Macroscopic and microscopic evaluations were performed, considering the integration of autografts and retraction of wound edges, as well as neovascularization, inflammatory infiltrate, young fibroblasts, collagenization, reepithelization and autografts integration. There was no difference between the groups (P > 0.05) in relation to most macroscopic and microscopic variables. However, neovascularization was significantly greater (p = 0.0191) in group T, on the 14th day after grafting. It is concluded that PRP favors the process of skin repair with autografts in horses, since it increases the neovascularization in the initial phase of wound healing. Furthermore, the PRP seems to positively influence the integration of the skin autografts and the retraction of the wound edges.